EMOTIONS IN MASS MEDIA DISCOURSE: A DISCOURSE-LINGUISTIC APPROACH - Alexandra Kalandarova (Modern American Journals, 2025)
This article examines emotions from a linguistic perspective and their role in media discourse. Emotions are analyzed as speech strategies functioning within a specific genre and multimodal environment. The aim of the article is to identify how media discourses encode, shape, and transmit emotions, influencing mass consciousness. The novelty of the study lies in its comprehensive approach to analyzing emotions in the media, taking into account both intratextual and intertextual levels.
Keywords: Media discourse, emotions, linguistics, emotions in language and text, emotional scripts.